PEMBUATAN MODEL ALAT PENGASAPAN IKAN LAUT PADA MASYARAKAT NELAYAN PANTAI TRISIK KABUPATEN KULON PROGO DIY - Lastariwati, Badraningsih (Universitas Negeri Yogyakarta, 2003)
The vucer program was aimed to realize a tool for smoking fish using liquid smoke techniql;1pwhich perforins optimal work, easy to use and maintain affordable, ergonimic and efficient.'Theprogram was started from July to November 2002. The partner of thisprogram was the fishermen group under TPI Mian Samudra, Trisik Beach, Kulon Progo, Yogyakarta .. T l activity was begun by making a tool for smooking fish, a specially designed'oven, then followed with the experiment of the tool in thelaboratory ofPKK-Bog , UNY. 'By creating a new tool to process smoked fish, it is hoped that it can producegood quality and quantitysmeked fish, as well as can save time and energy. With this tool, it means that it gives an opportunity for an industry to develop its product. Then it can increase the fishermen arid fish sellers' income.The product yielded from this program was a set of oven for smoking fish which is strong enough, easy to operate, with sufficie volume and simple quality control.Key words: fish smoking, smoked fish, and tool model